Kāmākhya, den menstruerende gudinde: Tantrisme for lægfolk og elite - Qvortrup Fibiger, Marianne (Religionsvidenskabeligt tidsskrift, 2019)
Based on an analysis of the cult around the tantric goddess Kāmākhya from Assam, I will discuss her appeal for both laypeople and ascetics. A special feature is that she menstruates and that her blood is held to have thaumaturgical as well as transformative properties. For laypeople the hope is that it will have a positive effect on their lives here and now, and for the ascetics that it will give rise to an internal process with a soteriological goal in mind. Consequently, I shall present a differentiation between a hardcore and a softcore tantrism and, furthermore, their interrelationship.